Visual Branding, Lifestyle Positioning, and Consumer Perception: How Instagram Shapes the Brand Image of an Urban Coffee Shop - Auzan Abi Nubli; Veranus Sidharta (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
This study examines how Instagram contributes to the formation of brand image through visual branding, lifestyle positioning, and consumer perception in the case of The Tables, an urban coffee shop in Jakarta. Using a qualitative case study approach, the research explores branding communication activities conducted through the Instagram account @thetables.jkt. Data were collected through in-depth interviews with internal stakeholders and consumers, non-participant observation of Instagram content, and digital documentation. The data were analysed using thematic analysis supported by NVivo to identify patterns related to visual branding, brand identity, lifestyle positioning, engagement, and consumer perception. The findings reveal that Instagram functions not merely as a promotional platform but as a symbolic space where brand identity and consumer experiences are continuously constructed. The Tables successfully differentiates itself through a consistent visual identity characterized by R&B culture, zebra symbolism, event-oriented content, and a distinctive ambiance. Consumers perceive the brand as more than a coffee shop, associating it with music, community, self-expression, and urban lifestyle experiences. The study also finds that while lifestyle-based branding effectively strengthens brand image and trust, it should be balanced with clearer product-related communication. Ultimately, brand image is shaped by the interplay among visual consistency, digital engagement, lifestyle positioning, and consumers' lived experiences.